Modelling of the microglial response to neuronal α-synuclein aggregation - Katsikoudi, A (2022)
Parkinson’s disease is the second most common neurodegenerative disease, characterised by α-synuclein aggregation and loss of dopaminergic and other types of neurons. Inflammation, the activation of microglial and other immune cells in response to pathology, is a well-documented feature of the neurodegenerative process. Yet, it remains unresolved whether inflammation prevents or promotes the degeneration of dopaminergic neurons in Parkinson’s disease. One reason for this knowledge gap is the lack of relevant human experimental models to study the interaction between neurons and microglia in response to pathological α-synuclein. In this study, I sought to establish human ex vivo and in vitro models to decipher the microglial response to neuronal α-synuclein aggregation that was triggered by the addition of de novo generated fibrils. Using mouse organotypic cultures, I showed that microglia are activated in response to aggregation. In a novel iPSC-based dopaminergic neuron-microglial co-culture model, I found that α-synuclein aggregation and aggregate-induced neuronal loss were mitigated by the presence of microglia. Gene expression studies and whole transcriptome analyses revealed an association between this beneficial phenotype and a transition from a homeostatic to a disease-related microglial gene expression profile. Further, pilot single cell RNA sequencing data revealed treatment specific clusters and biological pathways. Altogether my data showed that under certain conditions, microglia exert a beneficial effect in response to neuronal α-synuclein aggregation and identified morphological changes, cytokine secretion and disease-specific pathways that underpin this process. Further validation of these findings could offer immunological targets for disease modifying therapies in Parkinson’s disease.